Optimization of Gold Pawn Product Advantages to Increase Customer Base - Slamet; Rosidi, Mohammad; Riky, Moh. (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
The objective of this study is to examine the main characteristics that impact customer satisfaction with pawn products at BPRS Bhakti Sumekar, with a specific focus on its Waru Branch. Data for this study were gathered using a qualitative descriptive approach, through interviews conducted with the management, employees, and customers of BPRS Bhakti Sumekar's Waru Branch. In addition, supplementary data were acquired from papers, journals, and internal records of the bank. The research aims to maximize the benefits of gold pawn products in order to broaden the consumer base. BPRS Bhakti Sumekar, previously named BPR Bhakti Sumekar, is a Regional-Owned Enterprise (BUMD) located in Sumenep Regency. It was founded on September 16, 2002, first as a limited liability company (PT) before converting to a BUMD status. BPRS Bhakti Sumekar has a notable presence in the local financial sector with two Cash Offices and 28 Branch Offices, one of which is the Waru Branch.